2000
DOI: 10.1046/j.1440-1614.2000.00709.x
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressants versus placebo for the treatment of bulimia nervosa: a systematic review*

Abstract: The use of a single antidepressant agent was clinically effective for the treatment of bulimia nervosa when compared with placebo, with an overall greater remission rate and a higher rate of drop-outs. No differential effect regarding efficacy and tolerability among the various classes of antidepressants could be demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 33 publications
0
12
0
2
Order By: Relevance
“…The first limitation was the uncontrolled open trial design. As eating disorder patients have been shown to respond to placebo treatment (Bacaltchuk et al, 1999), we cannot exclude the possibility that the positive response to treatment was specifically in response to the sertraline treatment. Therefore, it will be important to examine the efficacy of sertraline in a double-blind, placebo-controlled trial that includes a larger sample size than that examined in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first limitation was the uncontrolled open trial design. As eating disorder patients have been shown to respond to placebo treatment (Bacaltchuk et al, 1999), we cannot exclude the possibility that the positive response to treatment was specifically in response to the sertraline treatment. Therefore, it will be important to examine the efficacy of sertraline in a double-blind, placebo-controlled trial that includes a larger sample size than that examined in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…A number of efficacious psychological interventions exist for bulimia nervosa (BN), including cognitive, behavioral, and family therapy (Wilson & Fairburn, 2002). Psychotropic medications are also frequently used to treat BN patients and studies have shown that several classes of medications are efficacious (Agras, 2001;Bacaltchuk, Hay, & Mari, 1999;Freeman, 1998). One of the most common classes of medications used with BN patients is the selective serotonin reuptake inhibitors (SSRIs; Agras, 2001), with fluoxetine receiving the most attention from investigators thus far.…”
Section: Introductionmentioning
confidence: 99%
“…The second systematic review found significantly higher withdrawal rates in people taking antidepressants than with placebo (12 RCTs, 10.5% v 5.1%) 29. It found no significant difference in withdrawal rates due to adverse effects among and within classes of antidepressants.…”
Section: Methodsmentioning
confidence: 96%
“…We found two systematic reviews, 21 29 two additional RCTs, 30 31 and two subsequent RCTs. 32 33 Versus placebo: Both reviews found that antidepressants reduced bulimic symptoms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation